2003
DOI: 10.1007/s11738-003-0041-0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of enzymatic scavengers of active oxygen species in rice in response to infection by Rhizoctonia solani

Abstract: Changes in the activities of peroxidase, ascorbate peroxidase, catalase and superoxide dismutase in rice in response to infection by Rhizoctonia solani were studied. A significant increase in peroxidase activity was observed in R. solani-inoculated rice leaf sheaths 1 day after inoculation and the maximum enzyme activity was recorded 3 days after inoculation at which period a 3-fold increase in peroxidase activity was observed compared to the untreated control. Three peroxidase isozymes viz., PO-4, PO-5 and PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 28 publications
4
3
0
Order By: Relevance
“…The highest POX activity was observed in the plants infected with R. solani (R and S + R groups). In agreement with our results, Paranidharan et al [72] found increased POX activities in rice in response to infection by Rhizoctonia solani. According to these results, we can speculate that increased lignin synthesis during both salt stress and pathogen infection in order to establish an apoplastic barrier and to make the cell wall less permeable to water loss might also be the case in our study [73].…”
Section: Discussionsupporting
confidence: 94%
“…The highest POX activity was observed in the plants infected with R. solani (R and S + R groups). In agreement with our results, Paranidharan et al [72] found increased POX activities in rice in response to infection by Rhizoctonia solani. According to these results, we can speculate that increased lignin synthesis during both salt stress and pathogen infection in order to establish an apoplastic barrier and to make the cell wall less permeable to water loss might also be the case in our study [73].…”
Section: Discussionsupporting
confidence: 94%
“…In the present findings in response to R. solani and T. virens separately, the activity of catalase increased at 1 dpi and 4 dpi in the resistant variety, whereas it was increased only at 4 dpi in the susceptible variety, but the combined response of these two upregulated the expression of catalase only in the resistant variety at 1 dpi and 4 dpi. The present findings are supported by the earlier observations that the catalase activity significantly increased in rice leaf sheaths at 2 days after inoculation with R. solani and reached maximum at 5 days after inoculation (Paranidharan et al 2003). Similarly, increased catalase activity was observed in inoculated apple fruits in combination of T. virens and Penicillium expansum in comparison with healthy control at all days of observations and the highest activity was noted at 6 days after inoculation (Bordbar et al 2010).…”
Section: Discussionsupporting
confidence: 91%
“…5A) and was increased 1.5-fold compared with the control. APX activity has also been observed in pepper infected by P. capsici [17], in rice in response to infection with R. solani [38], and in the relationship between R. solani and P. aeruginosa in rice [12]. We also found that APX from cucumber plants was present as three isoenzymes (Ap1, Ap2, and Ap3) ( Fig.…”
Section: Discussionsupporting
confidence: 74%